Menopausal Age of Differentiated Thyroid Carcinoma Patients after Single Dose of Radioiodine Therapy –Single Institute based Experience - Sharmin, Samira; Billah, Syed Muhammad Baqui; Rahman, Hosne Ara; Naznin, Afroza; Yasmin, Farida; Uddin, Md Monir (Bangladesh Journal of Nuclear Medicine, 2024)
Background: Menopause is a natural and unavoidable circumstance in all women.s lives. Radioiodine therapy is the most popular method of treatment for differentiated thyroid carcinoma (DTC) worldwide. Considering these two, this study was designed to evaluate the menopausal age of DTC patients after a single dose of radioiodine therapy. Patients and Methods: This is a retrospective study analyzed in INMAS, Mitford, Dhaka, from January 2018 to December 2019 among 225 female patients with DTC who were referred for radioiodine therapy of different doses according to their clinical state (75 mci (2.7 GBq), 100 mci (3.7 GBq), and 150 mci (5.5 GBq). Results: Among 225 patients, about 47 women (20.9%) experienced menopause after radioiodine therapy during this study period. The average age of menopause in Bangladeshi women is 46.7 years (95% CI). In this study, the mean menopausal age of the study subjects was 44.1±2.6 years. About 13 patients experienced menopause after 75 mci (2.7 GBq) radioiodine therapy with a mean age of 45.6±2.2; 28 patients had menopause after receiving 100 mci (3.7 GBq) with a mean age of 44.4±2.7; and 6 patients had menopause after receiving 150 mci (5.5 GBq) of I-131 with a mean age of 44.1±2.0. The result was significant (P<0.05). Conclusion: This study reveals that the mean menopausal age of the patients after radioiodine therapy is lower than the mean menopausal age of normal Bangladeshi women. Bangladesh J. Nuclear Med. 26(2): 129-132, 2023